Bidirectional DC-DC converter for microgrid in energy management system. Issue 2 (1st February 2021) - Rajasekaran, R.; Rani, P. Usha
ABSTRACT: DC-DC converter plays a major role in microgrid and energy storage system using operational stability and synchronised power delivery. In this paper, an energy management control algorithm is proposed based on closed-loop proportional-integral (PI) to solve and analyse the issues of unstable DC link voltage. During grid-connected mode, a hybrid energy storage system (HESS), i.e. super-capacitor (SC) and battery units are charged from different hybrid energy resource, i.e. solar and wind. In the absence of energy resources (solar or wind), the energy storage units (supercapacitor and battery) need to supply the grid, which is the main aim of this work. Initially, the energy management control is used to control the generated power from wind and solar for the stability requirement. The MPPT technique has been considered here to make system flexibility and compatibility with different PV cell and wind energy. This proposed system successfully tracked the maximum power, which is analysed using the combined development of galactic swarm optimisation (GSO) based incremental conductance (IC) algorithm. Using GSO in MPPT should reduce the steady-state oscillation and get high convergence rate. The whole work is implemented in Matlab/Simulink platform and the performance of proposed is compared with existing algorithms. Abbreviation : HESS: Hybrid Energy Storage System; MPT: Maximum PowerPoint; PWM: Pulse Width Modulation; SOC: State of Charge; PMSG: Permanent Magnet Synchronous Generator; PI: Proportional Integral; AC: Alternating Current; DC: Direct Current; GSO: Galactic Swarm Optimization